2015
DOI: 10.1590/s1516-89132015050290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant Growth Regulators on In Vitro Shoot Multiplication and Plantlet Formation in Cassia angustifolia Vahl

Abstract: An effective and improved plant regeneration system was successfully developed using shoot tip explants taken from a two years old mature plant of Cassia angustifolia. The effect of different cytokinins, , Kinetin (Kin)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The application of BA and NAA in M. communis caused a higher shoot multiplication rate (Nobre 1997;Scarpa et al 2000), while in vitro experiments of the rooting stage by Mascarello et al (2009) showed that the addition of a small amount of cytokinin caused better rooting of cultured material and a higher chlorophyll level. In the case of Cassia angustifolia, enriching the regulator free MS medium with cytokinins concentration not higher than 5.0 µM caused the induction and increased shoot multiplication rate (Siddique et al 2015). Nobre et al (2000) reported that BA concentration in the medium is the most important factor responsible for shoot multiplication of Viburnum tinus.…”
Section: Discussionmentioning
confidence: 99%
“…The application of BA and NAA in M. communis caused a higher shoot multiplication rate (Nobre 1997;Scarpa et al 2000), while in vitro experiments of the rooting stage by Mascarello et al (2009) showed that the addition of a small amount of cytokinin caused better rooting of cultured material and a higher chlorophyll level. In the case of Cassia angustifolia, enriching the regulator free MS medium with cytokinins concentration not higher than 5.0 µM caused the induction and increased shoot multiplication rate (Siddique et al 2015). Nobre et al (2000) reported that BA concentration in the medium is the most important factor responsible for shoot multiplication of Viburnum tinus.…”
Section: Discussionmentioning
confidence: 99%
“…Siddique et al (2015) achieved in vitro propagation of a medicinal species, Cassia angustifolia Vahl, and evaluated two cytokinins (BA, Kin) in the concentration of 1.12 mg L -1 and the auxin IAA (0.01, 0.08 or 0.17 mg L -1 ). They observed that BA was more effective than kinetin in promoting new shoot formation: the explants established in a culture medium with 1.12 mg L -1 BA and 0.08 mg L -1 IAA developed 8.7 shoots 5.6 cm in length.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro culture is a biotechnological tool consisting of an aseptic culture of different explants in a culture medium and incubation to make use of the totipotentiality of the cells to induce cell division, morphogenesis and plant development (Fortes and Pais, 2000;Siddique et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The previous study [23] observed (7.0±0.89) shoots and (5.3±0.26) shoots /explants on MS solid medium amended with TDZ and BAP respectively and [24] reported that maximum number of multiple shoots observed on solid medium with combination of 6.0µM BAP and 0.2 NAA (35.70± 0.97) in Oldenlandia biflora L. [25] observed that large number of multiple somnifera.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 85%